Response of mango (Magifera indica) to light pruning for vegetative and flowering flushes - Waghmare, G M; Joshi, G D (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2003-05 at mango research station. Rameshwar to regulate the vegetative flush for induction of uniform flowering in 'Alphonso' mango (Manifera indica L.). Light pruning at different intensities immediately after harvest of the previous season crop and second fortnight of September were recorded uniform vegetative flush. Significantly maximum leaves (13.26) were recorded in treatment 2.5 cm pruning immediately after harvesting, followed by 7.0 cm pruning immediately after harvesting (12.89) and 15.0 cm pruning immediately after harvesting (11.61). Significantly highest axillary buds in 2.5 cm pruning immediately after harvesting (3.71) treatment, followed by 7.0 cm pruning immediately after harvesting (3.52), 15.0 cm pruning immediately after harvesting (3.42) and are at par. Sex ratio was maximum in 2.5 cm pruning immediately after harvesting (1 1.53) subsequently fruit yield were also maximum in treatments 2.5 cm pruning immediately after harvesting (4.46 tonnes/ha) and 7.0 cm pruning immediately after harvesting (3.94 tonnes/ha) compared with the control.